COMPARATIVE ASSESSMENT OF DISCRETE ELEMENT METHODS AND COMPUTERIZED FLUID DYNAMICS FOR ENERGY ESTIMATION OF THE CULTIVATOR WORKING BODIES - Mudarisov, Salavat; Farkhutdinov, Ildar; Aminov, Raushan; Rakhimov, Zinnur; Bagautdinov, Rustem; Rakhimov, Ildar; Gainullin, Ilshat (Journal of Applied Engineering Science, 2020)
Computer modeling of various technological processes, including soil treatment, has currently become an urgent task. The purpose of the study is to make energy evaluation of the tilling implement working tool by modeling the technological process with the use of discrete element methods and the method of computerized fluid dynamics. The obtained results were compared with the results of real experiments. The paper presents the results of the comparative energy assessment of the cultivator's working tool. The results were obtained during real experiments conducted in the tillage bin by modeling the soil treatment technological process with the use of discrete elements (DEM) and computerized fluid dynamics methods (CFD). To measure the working tool tractive resistance in the tillage bin an experimental unit with strain indicators of 5000N rating value was created. The unit has the function of possible technological and structural adjustments. Soil particles configurations were selected by modeling the technological process with the use of the discrete elements method. Literature sources and data of various soil examinations were used to determine physical and mechanical properties of soil. Such values as Poisson's ratio (V), static friction coefficient (f), shear modulus (G), and Young’s modulus (E) were set. According to the results the values got using computerized fluid dynamics method are similar to the results of real experiments conducted in the tillage bin. When using discrete element modeling the value of the instrument tractive resistance is close to real data at low operating speeds.